The Definitive Guide to SQLite (Second Edition) - Allen, Grant (Apress, 2013)
The Definitive Guide to SQLite covers SQLite in a comprehensive fashion, giving you the knowledge and experience to use it in a wide range of situations. Whether you are a hard-core C developer, are a mobile device aficionado, or are just seeking more know-how on the best embedded and small-footprint database engine ever invented, this book it for you.